2015
DOI: 10.1038/jp.2015.163
|View full text |Cite
|
Sign up to set email alerts
|

Successful primary use of VVDL+V ECMO with cephalic drain in neonatal respiratory failure

Abstract: The VVDL+V approach can be used successfully as the primary approach for ECMO for neonatal respiratory failure of various etiologies and in this single-center cohort this approach was associated with improved survival and lower rates of complication as compared with the ELSO database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Neonates (less than 28 days) requiring ECMO for respiratory failure in the Level IV NICU at Childrenʼs Healthcare of Atlanta at Egleston between January 1, 2010 and December 1, 2016 were identified through a retrospective chart review of the institutional ECMO database; supplemental information was gathered from individual medical records. Patients undergoing ECMO support met our institution specific criteria for ECMO (Table S1, available as supporting information in the online version of this paper), and all patients treated during the time period were included in the study . The institutional review boards at Emory University School of Medicine and Childrenʼs Healthcare of Atlanta approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…Neonates (less than 28 days) requiring ECMO for respiratory failure in the Level IV NICU at Childrenʼs Healthcare of Atlanta at Egleston between January 1, 2010 and December 1, 2016 were identified through a retrospective chart review of the institutional ECMO database; supplemental information was gathered from individual medical records. Patients undergoing ECMO support met our institution specific criteria for ECMO (Table S1, available as supporting information in the online version of this paper), and all patients treated during the time period were included in the study . The institutional review boards at Emory University School of Medicine and Childrenʼs Healthcare of Atlanta approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…In our prior report on patterns of MRI brain injury in this population, all major infarctions were observed in the VA ECMO group and internal carotid artery narrowing was observed as a lasting sequelae of arterial cannulation post-ECMO, 16 given that our institutional practice included carotid ligation without vessel repair at decannulation during the study period. Of note, our institutional protocol includes use of a cephalad venous cannula for patients supported with VV ECMO which may be protective against neurological injury, 26 although this has been refuted by some studies 27 leading to institutional variability in this practice. This and other factors specific to institutional differences in ECMO management may affect the generalizability of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, many studies have reported the benefits of VV ECMO for neonatal respiratory failure. Roberts et al [25] in a single center study compared double-lumen venovenous extracorporeal membrane oxygenation with cephalic draining cannula (VVDL+V ECMO) with data as collected in the ELSO database, with survival rate of 89.1% and 68.7%, respectively. They concluded that VVDL+V approach was associated with improved survival and lower rates of complication as compared with the ELSO database.…”
Section: Discussionmentioning
confidence: 99%